BADAN PERADILAN KHUSUS PENYELESAIAN PERSELISIHAN HASIL PILKADA PERSPEKTIF NEGARA DEMOKRASI KONSTITUSIONAL - Fazlar Rusyda Kamila (Yayasan Merassa Indonesia Publikasi, 2024)
This study explores the urgency of establishing a special judicial body for resolving disputes over the results of regional head elections (pilkada) in the context of a constitutional democratic country. The Constitutional Court (MK) Decision Number 85/PUU-XX/2022 establishes the permanent authority of the Constitutional Court in handling disputes over election results, ending the discourse on the establishment of a special judicial body mandated by law but has not yet been realized. This decision raises concerns about the potential for case overload that could interfere with the effectiveness and efficiency of the Constitutional Court as the guardian of the constitution. This study aims to analyze the impact of the ruling on the principles of constitutional democracy and examine the extent to which the establishment of a special judicial body can strengthen or weaken the legal system in Indonesia. Through a normative juridical approach and descriptive analysis of the Constitutional Court's decisions and existing legal frameworks, this study examines the dynamics of legal power and function in its adaptation to actual needs and conditions, as well as the importance of maintaining the integrity of the constitution and democratic principles. The results of the study show that, although the Constitutional Court can guarantee constitutional harmony in the settlement of election disputes, there is an urgent need to evaluate the implications of the absence of a special judicial body to ensure a more focused and efficient legal system in handling certain types of cases.